A survey of dermatology residents and program directors assessing the transition to dermatology residency. Issue 1 (2nd January 2021) - Hopkins, Christina; Jalali, Omid; Guffey, Danielle; Dao, Harry
Abstract: The transition from internship to residency is a critical period for trainees. This study investigated factors that influence the transition of residents from postgraduate year 1 (PGY-1) to dermatology residency. In June 2019, a program director–specific survey and a resident-oriented survey were administered via Survey Monkey. An email containing survey hyperlinks was sent via the Association of Professors of Dermatology Listserv to program directors, who were asked to forward the email to their current trainees. A total of 44 dermatology residents and 33 program directors responded. More than 58% of program directors identified a preliminary year in internal medicine as most beneficial. Both residents and program directors indicated rheumatology, infectious disease, and allergy and immunology as the most relevant PGY-1 electives. Eighty-two percent of program directors expected <1 h/week or no independent preparation for dermatology residency during PGY-1. The stress of incoming residents as perceived by program directors was significantly less than the self-reported stress of residents during their transition to dermatology residency (Mann-Whitney U, two-sided, P = 0.011).